EFFECT OF ADDITION Spirulina sp. WITH DIFFERENT NUMBER OF QUALITY OF KEFIR MASK CREAM - Shyntya Yuniarti Dewi; Desmelati Desmelati; Dewita Buchari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT           This study aims to determine the effect of the addition of Spirulina sp. with different amounts andthe amount of appropriate addition to the quality of kefir mask cream.The method used in this study is the experimental method of making the kefir mask cream with the addition of Spirulina sp. The design used was Randomized Complete Random (RAL) non factorial with 4 treatment levels is M0 (0g), M1 (5g), M2 (10g), M3 (15g).The results showed that the level of consumer acceptance of the kefir mask cream Spirulina sp. with the highest values being the color onthe M3 treatment (53,75%), the texture on treatment M0 (66,25%) the odor on treatment of M3 (12,5%) and the likes of the M3 treatment (25%).Based on the analysis of variance, it is known that the best treatment is in the treatment of M3 that is the color (dark green), the smell (typical Spirulina sp.), the vise (viscosity), the drying time 15 minutes 9 seconds. The best texture and pH values resulted from M0 treatment with texture (soft) and pH (acid). The best homogeneity test results were found in the M0 treatment which showed homogeneity. Based on the results of the study that the number of Spirulina sp. Appropriate added to kefir mask cream that is 15 g (M3).Keywords: Spirulina sp., kefir mask, consumer acceptance